2004
DOI: 10.1385/bter:102:1-3:199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Fluorosis on Lipid Peroxidation and Histology of Kidney Tissues in First- and Second-Generation Rats

Abstract: This experiment was designed to investigate the lipid peroxidation and histological effects of chronic fluorosis on first- and second-generation rat kidney tissues. Sixteen virgin female Wistar rats were mated with eight males (2: 1) for approx 12 h to obtain first-generation rats. Mating was confirmed by the presence of sperm in vaginal smears. Sperm in vaginal smears was observed in 10 of 16 rats (d 0). These rats were identified as pregnant and included in this experiment. Pregnant rats were divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 25 publications
0
29
1
5
Order By: Relevance
“…Wistar rats, exposed to high fluoride doses, also showed enhanced LPO in their RBCs [108][109][110][111], liver [108,110,111], and brain [108,110]. Karaoz et al [112] showed that exposure of the pregnant rats and their offsprings during first month of life to fluoride leads to kidney tissue changes and LPO in the first and second generation of rats. A direct link between fluoride-induced apoptosis and elevated LPO was shown in the pig [30] and rat [31] hepatocytes.…”
Section: Lipid Peroxidationmentioning
confidence: 99%
“…Wistar rats, exposed to high fluoride doses, also showed enhanced LPO in their RBCs [108][109][110][111], liver [108,110,111], and brain [108,110]. Karaoz et al [112] showed that exposure of the pregnant rats and their offsprings during first month of life to fluoride leads to kidney tissue changes and LPO in the first and second generation of rats. A direct link between fluoride-induced apoptosis and elevated LPO was shown in the pig [30] and rat [31] hepatocytes.…”
Section: Lipid Peroxidationmentioning
confidence: 99%
“…Moreover, thyroid gland has been reported to have a strong capacity for absorbing and accumulating fluoride [11]. Indeed, previous laboratory investigations have demonstrated that excessive exposure to fluoride caused histopathological damage and altered the functional responses of the kidney and thyroid gland [12,13]. Moreover, endemic fluorosis is a global concern because several millions of people are affected.…”
Section: Introductionmentioning
confidence: 99%
“…The study of more than one generation allows detection not only of any effects on adult reproduction but also of effects on subsequent generations due to exposure in utero and early postnatally. The latest evaluation of sodium fluoride administration through multiple generations has been made previously in general aspects by Collins et al [18,19], in the myocardium, lung, kidney, and testis by Cicek et al [20], Aydin et al [21], Karaoz et al [22], and Meral et al [23] respectively, but brain tissue has not been studied specifically in multigeneration animals. Due to the lack of information on multigeneration studies concerning fluoride-induced changes on the thyroid hormone status, the histopathology of discrete brain regions, and the resultant alterations in acetylcholine esterase levels and the learning and memory abilities, the present study was undertaken.…”
mentioning
confidence: 99%